Small GTPase RHOE/RND3, a new critical regulator of NF‐κB signalling in glioblastoma multiforme?. (22nd July 2019) - Sun, Qian; Dong, Huimin; Li, Yuntao; Yuan, Fan'en; Xu, Yang; Mao, Shanping; Xiong, Xiaoxing; Chen, Qianxue; Liu, Baohui
Abstract: Objectives: Abnormal activation of NF‐κB signalling is a major mechanism of apoptosis resistance in glioblastoma multiforme (GBM). Therefore, better understanding of the regulation of NF‐κB signalling has a significant impact for GBM therapy. Here, we uncovered a critical role of the small GTPase RND3 in regulating the p65 subunit of NF‐κB and NF‐κB signalling in GBM. Materials and methods: Human GBM samples, GBM cells and a human orthotopic GBM‐xenografted animal model were used. The mechanisms of RND3 in regulation of NF‐κB signalling and GBM cell apoptosis were examined by luciferase assay, quantitative PCR, immunostaining, immunoblotting, immunofluorescence, coimmunoprecipitation, TUNEL staining, JC‐1 analysis and flow cytometry. Results: Overexpression of RND3 led to reduced p65 activity in GBM‐cultured cells and a GBM animal model, indicating that the NF‐κB pathway is negatively regulated by RND3 in GBM. Mechanistically, we found that RND3 bound p65 and promoted p65 ubiquitination, leading to decreased p65 protein levels. Furthermore, RND3 enhanced cleaved caspase 3 levels and promoted apoptosis in GBM cells, and RND3 expression was positively correlated with cleaved caspase 3 and IL‐8 in human GBM samples. The effect of RND3 on promoting apoptosis disappeared when p65 ubiquitination was blocked by protease inhibitor carfilzomib or upon co‐expression of ectopic p65. Conclusions: RND3 binds p65 protein and promotes its ubiquitination, resulting in reduced p65 protein expression and inhibition of NF‐κB signalling to induce GBM cell apoptosis.